The Women-Based Welfare (WBW): Penguatan Perempuan Berbasis Formulasi Government Expenditure di Kabupaten Gunungkidul DI Yogyakarta - Setiawan, Hendy; Erison, Yendra (Bestuurskunde: Journal of Governmental Studies, 2023)
Women have played an important role in welfare development through government spending. There is a tendency for areas with a low level of welfare to be synonymous with development that does not provide space and opportunities for women. Whereas in reality women are part of the welfare element itself. This research uses a qualitative approach with the method of literature study. The author collects data through various relevant literature, either in online media, official media, and other literature. Meanwhile, researchers in carrying out this research stage used the Creswell concept. The stages of this research consisted of problem identification, literature search, research aims and objectives, data collection, data analysis and interpretation, and research reporting. The results of the study show that the low level of welfare in Gunungkidul is in line with the weak condition of women in the development budget. This can be traced with the logical implications of the development indicators that have been implemented in Gunungkidul. For example, if you see a high poverty rate, a weak human development index, a weak gender development index, and a low gender empowerment index, this shows how fragile well-being is from within. This is also relevant to the revenue budget, especially from tax collections which are also weak, reinforcing how welfare issues are still a problem today. Therefore, the main key in advancing welfare development in Gunungkidul is placing women not only as objects but also as subjects in building welfare that is inclusive and fair.